Nepal-Britain treaty 1923: Nepal’s achievements and legacies - Bhandari, Dadhiram (Journal of Management and Development Studies, 2023)
Nepal’s independent status has largely been shaped by historical events, personalities, treaties, and agreements. Domestic and external events that happened in the first two decades of the twentieth century had and continued to have a direct impact on Nepal’s external behavior and independence. During that period, Nepal was deeply engaged in war with British-India and Tibet as well as in World War-I. Nepal’s deep involvement in regional and global affairs resulted in the conclusion of the treaty between the United Kingdom and Nepal in 1923 A.D. which helped consolidate Nepal’s independent status thereafter. Against this backdrop, a descriptive analysis of the historic events such as Chandra Shamsher's rule in Nepali politics, Lord Curzon’s arrival in India as British-India’s Viceroy, the Lhasa Mission 1903-04, Nepal’s involvement in World War-I and the Hunting Diplomacy of Nepal are described in this article mainly to explain their contributions to the 1923 Treaty. The provisions of the treaty have also been examined with a view to assessing its contributions to the independence of Nepal. In short, it is an effort to argue on Chandra Shamsher's diplomatic success to consolidate Nepal’s independence through a treaty between the United Kingdom and Nepal in 1923. In the short run, that treaty contributed to Nepal’s international recognition as an independent sovereign country setting it aside from other Indian princely states. In the long run, it contributed to building a distinct international identity of Nepal.